Highland Park and River Oaks : the origins of garden suburban community planning in Texas - Ferguson, Cheryl Caldwell, 1953- (Roger Fullington series in architecture., 2014)
"Shows how the developers of Highland Park in Dallas and River Oaks in Houston were trying to create better living conditions in a countryside atmosphere away from the uncontrolled development that had blighted late 19th-century and early 20th-century urban neighborhoods in Texas. Also explores why planned suburban and community growth failed at the city-wide level and remained confined to elite suburbs. Also looks at subdivisions in Fort Worth, San Antonio, Amarillo, Wichita Falls, Beaumont, Galveston, and Port Arthur to provide information on how city planners worked with landscape architects to incorporate infrastructure improvements, coordinate landscape planning, and employ such legal devices as restrictive covenants to shape elite space coherently. The work of Texas' foremost suburban house architects, such as C.D. Hill, William Ward Watkin, and John F. Staub, is also analyzed"--